ECOLOGY AND EPIZOOTIOLOGY OF TREMATODOSIS IN CATTLE, TREATMENT AND PREVENTION IN DAIRY CATTLE FARMS OF VOLOGDA REGION - A. L. Kryazhev (Российский паразитологический журнал, 2016)
Objective of research: To study the epizootiology of trematodoses of cattle from dairy cattle farms in the Vologda region; to estimate the anthelmintic efficacy of Fascocide, Helmicide, Oxiclozanide, Albendazole, Fezole, Alben.Materials and methods: A preliminary analysis of veterinary reports of the Department of Veterinary Medicine, the regional Stations on Fight against Diseases in Animals, meat-processing plants and slaughter units, Laboratories of Veterinary and Sanitary Expertise was carried out for the period 2005–2009 according to the Forms «1-Vet» and «5-Vet». Coproovoscopic examinations of cattle were conducted monthly to determine seasonal and age dynamics of infection. Biological features of intermediate hosts were studied by standard methods. Fascocide at the dose of 10 mg a.i./kg, Helmicide — 7,5 g/100 kg, Oxiclozanide — 5,25 mg/kg, Albendazole — 15 mg a.i./kg and Alben — 10 mg a.i./kg were used against fasciolosis and paramphistomosis in cattle under production conditions in dairy farms and complexes of Vologda region.Results and discussion: The rates of trematode infection in various climatic and geographic zones of the region are different. The highest level of infection was registered in the North Eastern and South Eastern zones, and the lowest — in the South Western.Adult cattle are infected with Fasciola hepatica, Paramhistomum cervi and P. ichikawai all year round; the maximum peak of infection is registered in winter and spring seasons. First signs of trematode infection in calves of the first grazing season are observed at the beginning of the pasture season, which is the evidence for the overwintering of helminth larvae in intermediate hosts. Trematode infections manifest commonly as mixed infections.First individuals of Lymnaea truncatula and Planorbis planorbis appear in biotopes in the second decade of May, reaching the maximum number in August. Their infection with trematode parthenites is observed in the period from the first half of June to October; the maximum peak of infection — in August. The most effective preparations for dehelmintization against Fasciola spp. and Paramhistomum spp. are Fascocide, Helmicide and Fezole.